New data on phylogeography of the boreal owl, Aegolius funereus (Strigiformes, Strigidae), in Eurasia - Homel, K. V.; Nikiforov, M. E.; Kheidorova, E. E.; Valnisty, A. A. (Zoodiversity, 2020)
In the article the research’s results of phylogeography, genetic diversity, genetic structure and demographic characteristics of the boreal owl population in Eurasia are given. The first domain of control region of mtDNA is used as a genetic marker. The sample size was 59 specimens. The population of boreal owl is characteristic of high genetic diversity and it has signs of rapid expansion in the past as revealed by analysis of CR1 mtDNA polymorphism. Genetic differentiation between birds from the west and the east part of the species range is shown. The level of found population genetic differentiation isn’t high that can be explained by gene flow in the past and possible at the present time. We didn’t reveal any signs of genetic differentiation for boreal owl population according to subspecies (between A. f. funereus and A. f. pallens) which are distinguished for the studying area.